1980
DOI: 10.1136/jcp.33.12.1153
|View full text |Cite
|
Sign up to set email alerts
|

Megakaryocytes in pleural and peritoneal fluids: prevalence, significance, morphology, and cytohistological correlation.

Abstract: SUMMARY Over a period of 22 years, 4844 pleural and peritoneal fluids from 3279 patients were examined cytologically. Megakaryocytes were found in the fluids from five patients. The clinical diagnoses in the five patients were agnogenic myeloid metaplasia, chronic myeloid leukaemia, and lymphocytic lymphoma. All of these patients had persistent serous effusions. Megakaryocytes in serous fluids occurred in three forms: (1) a large type with abundant cytoplasm and multilobed nuclei, (2) a smaller type with a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 4 publications
1
31
0
Order By: Relevance
“…Kumar and Naylor (6) reported that the pleural or peritoneal fluid from 5 out of 3,279 patients contained megakaryocytes, and three of them were IMpatients. Twoof the patients underwent autopsies, and the foci of ectopic hematopiesis was found on the serous surface (1 1).…”
Section: Discussionmentioning
confidence: 99%
“…Kumar and Naylor (6) reported that the pleural or peritoneal fluid from 5 out of 3,279 patients contained megakaryocytes, and three of them were IMpatients. Twoof the patients underwent autopsies, and the foci of ectopic hematopiesis was found on the serous surface (1 1).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, two large retrospective analyses of EHE revealed the most common primary diseases associated with EHE to be myelofibrosis (1) and lung cancer (2). Reports of EHE accompanied by malignant lymphoma have been limited thus far and lack detailed clinical data (1,2). We herein report a case of EHE accompanied by follicular lymphoma (FL).…”
Section: Introductionmentioning
confidence: 96%
“…Extramedullary hematopoietic effusion (EHE), including pleural, peritoneal and pericardial effusion, is widely accepted to be a rare manifestation accompanied by hematologic disorders and neoplastic diseases (1)(2)(3)(4)(5). Due to its rarity, most reports are case reports.…”
Section: Introductionmentioning
confidence: 99%
“…The finding of extramedullary hematopoiesis in the serosa surfaces has seldom been reported [1][2][3]5], but may be associated with marked and persistent ef fusion [1,2,[6][7][8].…”
Section: Discussionmentioning
confidence: 99%